Fuzzy Topsis System Untuk Pemilihan Karyawan Terbaik Pada PT. Delta Dunia Textile - Arif Wicaksono Septyanto; Nugroho Arif Sudibyo; Ardymulya Iswardani; Tiyan Ganang Wicaksono (UNIVERSITAS INDO GLOBAL MANDIRI)
This research implements a fuzzy topsis based system for selecting the best employees at PT. Delta World Textil. One of the matters, especially in the management of Human Energy Resources (HR) is the selection of the best employees periodically, so that those who are elected will be given an award in the form of a bonus in order to motivate employees to improve their service and performance. The best and quality employees are the legacy of the industry that wants to make the industry grow rapidly. Several methods have been proposed for selecting the best employees. However, the method used is inaccurate because it only uses one method with few criteria. This study aims to select the best employees by looking at several criteria in the form of discipline, teamwork, attitudes, presence, skills, loyalty, tenure, and productivity for initial processing using fuzzy logic. Initial values are obtained in the form of membership function values which are used as input into the topsis method. The first stage of the topsis method is carried out in the normalized decision metric stage, the results of this stage are used to find a weighted normalized decision matrix according to the weight of the criteria for each criterion, the results of this stage are used to ensure positive ideal solving and negative perfect solutions after that the distance between the values is determined. each alternative with a positive perfect solution matrix and a negative perfect solution matrix. In the last session, the highest preference value was sought so that the best employees were obtained. The results show that the system established is very feasible in ensuring the best employees in performance evaluation. Keywords : Fuzzy Logic, Topsis, Best Employees, Decision Support System